Evaluation of ukrainian waterworks positive impact factors upon environment, industrial, agricultural and social spheres - Бенатов, Даніель Емілович (Eastern-European Journal of Enterprise Technologies, 2014)
Hydrotechnical constructions of energy and water facilities play important role in the modern Ukrainian economics. There’re about 300–350 reservoirs of more than 10 000 m3 and many small reservoirs for various purposes with about 100 hydroelectric power plants (HPP) and thermal power plants (TPP) on them. Their operation is risky due to possible disasters and their catastrophic effects with significant financial and human losses. Therefore safe operation of hydrotechnical constructions is an important element of national security. Except for several exceptions, the vast majority of modern scientific works in the field of technological and environmental safety is primarily devoted to waterworks’ negative impact on the environment. The researchers often neglect evaluation of their industrial, social, recreational and ecological potential. Our work presents: – system classification of Ukrainian waterworks facilities positive impact factors upon environmental, industrial, agricultural and social sectors; – collection, systematization and analytical processing of information relating to 18 largest Ukrainian waterworks facilities, which determine value of the integral index of positive effects for each object. The study confirmed: said facilities are involved in many areas of social life, apart from electricity production. Analysis of the results showed that the waterworks facilities potential has not been used in full. This especially concerns large reservoirs of the Dnieper cascade and Dniester reservoir, while smaller reservoirs have a well-developed economic and recreational infrastructure. Management recommendations for local executive and governing bodies, which are responsible for the operation of researched facilities, are to be developed on the basis of obtained data.